Molluscum Contagiosum Associated with Acquired Immunodeficiency Syndrome: Experience in HIV outpatient care and literature review - Encarnacion, Paloma Marianni Suazo; Garzon, Ivan Mauricio Herrera; Martins, Carlos José; Lima, Ricardo Barbosa; Ferry, Fernando Raphael de Almeida (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Molluscum contagiosum is a dermatosis caused by a DNA virus of the family Poxvirus and genus Molluscipoxvirus, affecting mainly children, sexually active adults, atopic individuals and immunocompromised patients, especially those with human immunodeficiency virus (HIV) infection. Objective: To describe our experience in caring for patients living with HIV who presented with extensive and severe Molluscum contagiosum, and to conduct a literature review on the subject as well. Methods: An electronic search was carried out in the MEDLINE/PubMed and SciELO databases and in the books: ATLAIDS and AZULAY limited to the period of January 2017 to June 2021. Results: Four clinical cases are reported in people living with HIV with extensive lesions normally not found in immunocompetent patients. The treatment performed in the cases reported in this article was the punctual application of 90% trichloroacetic acid (TCA) to each lesion, with complete remission of the clinical presentation in two patients over a period of three and six months. The other two patients did not receive treatment for molluscum contagiosum as they died because of pulmonary complications. Conclusion: Infection with Molluscum contagiosum in people living with HIV has disseminated forms with large-volume lesions, with substantial stigmatizing aesthetic impairment, and treatment with 100% TCA is quite effective.